Levels of estradiol and testosterone are altered in Chinese men with sexual dysfunction. (6th May 2016) - Wu, F.; Chen, T.; Mao, S.; Jiang, H.; Ding, Q.; Xu, G.
Summary: An estimated 20–30% of adult men have at least one manifestation of sexual dysfunction, the most common of which are premature ejaculation (PE) and erectile dysfunction (ED). Emerging evidence has suggested an association between the regulation of hormones with the processes of erection and ejaculation. In this study, we aim to investigate the relationship between sexual dysfunction, namely, PE and ED, and the levels and ratios of estradiol to testosterone in Chinese men. A retrospective case–control study was performed involving 878 male patients aged from 18 to 74 years (mean: 36 years). The ratio of estradiol to testosterone was significantly higher for subjects with ED (7.45 ± 3.09 × 10 −3 ; p < 0.001), and combined PE and ED (6.66 ± 3.05 × 10 −3 ; p = 0.032) compared with that of the control group (6.01 ± 2.61 × 10 −3 ). The ratio was also significantly higher for ED patients when compared with PE patients (5.26 ± 2.18 × 10 −3 ; p < 0.001). Furthermore, compared with the control group, subjects with PE had similar levels of estradiol (95.47 ± 37.86 pmol/L vs. 94.12 ± 32.32 pmol/L; p = 0.678) but significantly higher levels of testosterone (18.66 ± 6.03 nmol/L vs. 16.82 ± 4.93 nmol/L; p < 0.001). This contrasted with the ED group, which showed similar levels of testosterone (16.96 ± 5.86 nmol/L vs. 16.82 ± 4.93 nmol/L; p = 0.773) and significantly higher levels of estradiol (116.88 ± 40.81 pmol/L vs. 94.12 ± 32.32 pmol/L; p < 0.001) compared with control. Subjects with combined ED and PE also had a significantly higher level of estradiol (104.98 ± 43.99 pmol/L vs. 94.12 ± 32.32 pmol/L; p = 0.014) and similar levels of testosterone (17.30 ± 7.23 nmol/L vs. 16.82 ± 4.93 nmol/L; p = 0.503) compared with control. In conclusion, this study involving Chinese males with sexual dysfunction reports, for the first time, that there is an association between sexual dysfunction and changes in levels of estradiol and testosterone. Further studies are required to ascertain the role of sexual hormone regulation in sexual function.